Clinical implementation and validation of a new indigenously designed cost-effective blood irradiation phantom box for use with linear accelerator - Sowmiya Sampathrajan; Kesavan Govindaraj; Arunkumar Nandagopal; Senthilkumar Shanmugam (Annals of Oncology Research and Therapy, 2025)
AIM: Irradiation of blood components is one of the proven methods of preventing the risk of transfusion-associated graft versus host disease (TA-GVHD). It is done using a dedicated blood irradiation device based on cesium-137 or cobalt-60 source or linear accelerator for lymphocyte suppression without damage to other blood cells. The main aim of this study is the clinical implementation of an indigenously designed, cost-effective blood irradiation phantom. MATERIALS AND METHODS: A blood irradiator phantom box was designed using Polymethylmethacrylate of outer dimension 33 cm × 38 cm × 11 cm and inner dimension 25 cm × 30 cm × 6 cm to accommodate a maximum of 6 blood bags. A marker is provided on the top and lateral sides of the phantom for easy alignment along the central axis of the beam. In our study, five freshly collected CPD-A blood bags were irradiated. The computed tomography scan images of the phantom with a Farmer chamber were taken. The prescribed dose was 25Gy and delivered using two parallel opposed iso centric beams covering the phantom. Blood samples were withdrawn from the blood bag prior to irradiation and after irradiation on Day 0, Day 7, Day 14, and Day 28, stored in a cold chain, and subjected to various biochemical and hematological tests. RESULTS: The progressive increase in serum potassium and lactate dehydrogenase levels in irradiated samples in comparison with nonirradiated samples was not statistically significant. Plasma hemoglobin levels, RBC count, and percentage hemolysis did not have much variations over time and were within acceptable limits, indicating the suitability of the product for transfusion. Quality assurance checks with Farmer chamber, and Gafchromic EBT3 film confirmed the accuracy of the dose delivered to blood bags. CONCLUSION: Hence, this study demonstrates the effectiveness of the indigenously designed, blood irradiation phantom box for use with linear accelerator, especially in developing countries without dedicated blood irradiator, at affordable cost.